Does foreign direct investment synchronise business cycles? Results from a panel approach - Claudia Fries; Marcus Kappler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This study readdresses the determinants of business cycle synchronisation. We test, on the one hand, whether FDI promoting policies may have consequences for the business cycle comovement between countries, and on the other hand, whether more plausible identification strategies change previous results. Our results suggest that linkages through foreign direct investment contribute in most cases positively to the synchronisation between country pairs. In contrast, the beneficial effects of trade integration for the similarity of business cycles are less robust and thus less important for the transmission of idiosyncratic shocks between countries than previously thought. Finally, we find that larger differences in the sector structure between two economies result in a bigger gap between their business cycles.
urn:nbn:de:bsz:180-madoc-393437
Keywords: F21; F41; F44; F49; 330; Business Cycle Synchronisation; FDI; Trade; Sectoral Differences; Panel